Federalism, decentralization, and economic growth - Lars P. Feld; Horst Zimmermann; Thomas Döring (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2004)
The distribution of competencies between the different levels of a federal system may have remarkable effects on economic growth, because mainly the regions of a country contribute to national economic development. Thus, a governments economic policy is reasonably shaped along regional lines. The theoretical discussion in economics focuses however on the efficiency aspects of a decentralized provision and financing of public services; rarely the argument is raised that decentralization or federalism increases growth through a higher ability of the political system to innovate and to carry out reforms. After a discussion of the theoretical arguments on federalism and growth, we address the empirical question in this paper how important the assignment of decision making competencies and the design of fiscal federalism are for economic development. Finally, on the basis of existing theoretical and empirical studies on economic growth and federalism, open questions and possible ways of answering them are presented.
Keywords: 330; Finanzföderalismus; Steuerwettbewerb; Wirtschaftswachstum; Theorie; Welt